Analisis Kinerja Simpang Tiga Tak Bersinyal (Studi Kasus: Jalan Yulius Usman- Jalan Sulawesi, Kota Malang) - Ama, Ignasius Tamo; Arifianto, Andy Kristafi; Rahma, Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
The unsignalized triple intersection of yulius usman- sulawesi road in malang city has a high level of density. Therefore, the amount of traffic passing through this intersection has increased significantly, resulting in high congestion during peak hours due to the presence of Pertamina gas stations and nearby businesses. The purpose of this study was to identify the characteristics, performance, and projection of the intersection for the next five years. This study uses a quantitative research approach, which is a type of descriptive evaluative research with data collection that allows researchers to document actual events that occur, one of which is a traffic volume survey conducted using the average traffic survey method (LHR). The results of the research for one week showed a maximum peak hour volume of 1884 skr/hour, the highest capacity of 2383 skr/hour, and the highest degree of 0.79 resulting in level of service D (Medium) and meeting the required value DJ PKJI 2014, <0.85. Based on the prediction of the intersection performance five years ahead, DJ = 1.18 is greater than > 0.85. This indicates that the level of service is F (very high) which has characteristics of very high traffic density and low volume and experiences congestion for a long time.